1989
DOI: 10.1111/j.1440-1681.1989.tb01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on a New Non‐invasive Monitor of Skin Blood Flow

Abstract: 1. A 'tissue perfusion monitor' (TPM) to non-invasively provide an index of skin blood flow (SkBF) has been developed; it employs photoelectric plethysmographic principles to measure changes in the nett flux of red blood cells in superficial microvasculature. 2. The 'tissue perfusion index' (TPI) varies in proportion to SkBF, provided local haemoglobin concentration does not change significantly. TPI of humans and experimental animals has been shown to indicate reliably, well established phenomena such as decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 22 publications
0
43
2
1
Order By: Relevance
“…3 The tissue PI varies with the quantity of red blood cells in the skin microvasculature and it is a reliable indicator of changes in skin blood flow (BF) in humans and animals. 4 The amplitude waveform of the pulse oximeter can be used as a noninvasive measurement of volume status in critically ill adult patients. 5 It has recently been reported that a foot skin PI value r1.24 is an accurate predictor of illness severity in neonates, 3 and a PI value r1.4 indicates hypoperfusion in adults.…”
Section: Introductionmentioning
confidence: 99%
“…3 The tissue PI varies with the quantity of red blood cells in the skin microvasculature and it is a reliable indicator of changes in skin blood flow (BF) in humans and animals. 4 The amplitude waveform of the pulse oximeter can be used as a noninvasive measurement of volume status in critically ill adult patients. 5 It has recently been reported that a foot skin PI value r1.24 is an accurate predictor of illness severity in neonates, 3 and a PI value r1.4 indicates hypoperfusion in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Movement artifacts during exercise were eliminated by suspending the arm at the level of the heart, in a sling fastened to the frame of the bicycle ergometer. Skin blood flow was measured with a laser Doppler probe mounted on the upper side of the forearm close to the strain gauge (Perimed PF2B), and with spectrophotometric probes (tissue perfusion monitor; Hales, Stephens, Fawcett, Daniel, Sheahan, Westerman & James, 1989) fixed with double-sided tape on forearm, finger, chest and forehead. These measurements and results will be described elsewhere (Hales, Nielsen & Yanase, manuscript in preparation).…”
Section: Recorder)mentioning
confidence: 99%
“…A calibration curve for laser Doppler instruments has been attempted by comparison with other methods evaluating various (and different) aspects of cutaneous circulation, such as venous occlusion plethysmography [18], radioactive microsphere injection [19], PPG [19,20], 133 Xe clearance [13,14,[21][22][23].…”
Section: Practical Applications and Use Of Ldf Methodologymentioning
confidence: 99%
“…PPG has been used in a variety of applications dealing with the monitoring of skin microcirculation during reactive hyperaemia, exercise and effects of topically applied products [19,45].…”
Section: Photoplethysmographymentioning
confidence: 99%